2012
DOI: 10.1016/j.febslet.2012.11.004
|View full text |Cite
|
Sign up to set email alerts
|

miR‐137 inhibits the proliferation of lung cancer cells by targeting Cdc42 and Cdk6

Abstract: a b s t r a c tMicroRNAs (miRNA) have emerged as key players in carcinogenesis. Here, we investigated the role of miR-137 in the pathogenesis of lung cancer. The downregulation of miR-137 in lung cancer cells could be rescued following inhibition of DNA methylation. Ectopic expression of miR-137 in lung cancer cells significantly downregulated Cdc42, Cdk6 and induced G1 cell cycle arrest, leading to a significant decrease in cell growth in vivo and in vitro. Further, both Cdc42 and Cdk6 were confirmed as targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
110
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(114 citation statements)
references
References 39 publications
4
110
0
Order By: Relevance
“…As previously described, 36 proteins from cells or tissues were separated by dodecyl sulfate, sodium salt-Polyacrylamide gel electrophoresis (SDS-PAGE) and then transferred to polyvinylidene difluoride membranes (Bio-Rad, CA, USA). The membranes were blocked and then probed with antibodies against Sp1 (sc-420), Cdk6 (sc-177), P-gp (sc-55510), Cyclin D1 (sc-753), vascular endothelial growth factor (VEGF) (sc-152) (Santa Cruz Biotechnology), pRb (R3403) or b-actin (A9044, Sigma, St. Louis, MO).…”
Section: Western Blot Assaymentioning
confidence: 99%
“…As previously described, 36 proteins from cells or tissues were separated by dodecyl sulfate, sodium salt-Polyacrylamide gel electrophoresis (SDS-PAGE) and then transferred to polyvinylidene difluoride membranes (Bio-Rad, CA, USA). The membranes were blocked and then probed with antibodies against Sp1 (sc-420), Cdk6 (sc-177), P-gp (sc-55510), Cyclin D1 (sc-753), vascular endothelial growth factor (VEGF) (sc-152) (Santa Cruz Biotechnology), pRb (R3403) or b-actin (A9044, Sigma, St. Louis, MO).…”
Section: Western Blot Assaymentioning
confidence: 99%
“…miRNAs are endogenous non-coding 19-23 nucleotide long RNA molecules that are located on chromosome 1p22. It has been revealed that miRNAs can downregulate gene expression by binding to the 3' untranslated regions (3'UTRs) of mRNA (6), thus affecting the proliferation, and metastasis of numerous types of cancer, such as gastric (7), breast (8) and lung cancer (9,10). The expression of miR-137 has been identified to be significantly downregulated in lung cancer compared with healthy lung tissue (11).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the downregulation of miR-137 in lung cancer cells may be rescued following treatment with a DNA methylation inhibitor. Furthermore, miR-137 has a tumor suppressor function by directly targeting cell division cycle 42 (CDC42) mRNA to inhibit the proliferation and invasion of colorectal cancer cells (10). miR-137 has been revealed to be upregulated following preoperative capecitabine chemoradiotherapy in rectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…46 Blockage of CDK6 expression by microRNAs (miRNAs) has been shown to inhibit the proliferation of gliomas, medulloblastoma, prostate, bladder, gastric, hepatocellular, and lung cancer cells, indicating the significant role of CDK6 in the initiation and progression of these cancers. [51][52][53][54][55][56][57][58] These observations, coupled with the fact that mice lacking D-type cyclins and/or CDK4/6 are viable, make targeting components of the CDK4/6 cyclin D-INK4-pRb-E2F pathway a highly attractive anti-cancer strategy. 12,14 CDK6 and hematological malignancies Acute myeloid leukemia (AML) is a malignant transformation of hematopoietic cells characterized by an increase in the number of myeloid cells in the marrow and an arrest in their maturation.…”
Section: Introductionmentioning
confidence: 99%